The Association Between Oxidative Stress and Depressive Symptom Scores in Elderly Population: A Repeated Panel Study - Changwoo Han; Youn-Hee Lim; Yun-Chul Hong (Korean Society for Preventive Medicine, 2016)
Objectives Previous epidemiological studies about oxidative stress and depression are limited by hospital-based case-control design, single-time measurements of oxidative stress biomarkers, and the small number of study participants. Therefore, in this study, we analyzed the association between biomarker of oxidative stress and depressive symptom scores using repeatedly measured panel data from a community-dwelling elderly population. Methods From 2008 to 2010, a total of 478 elderly participants residing in Seoul, Korea, were evaluated three times. Participants underwent the Korean version of the Short Form Generic Depression Scale (SGDS-K) test for screening depression, and urinary malondialdehyde (MDA) levels were measured as an oxidative stress biomarker. We used a generalized estimating equation with a compound symmetry covariance structure to estimate the effects of oxidative stress on depressive symptom scores. Results A two-fold increase in urinary MDA concentration was significantly associated with a 33.88% (95% confidence interval [CI], 21.59% to 47.42%) increase in total SGDS-K scores. In subgroup analyses by gender, a two-fold increase in urinary MDA concentration was significantly associated with increased SGDS-K scores in both men and women (men: 30.88%; 95% CI, 10.24% to 55.37%; women: 34.77%; 95% CI, 20.09% to 51.25%). In bivariate analysis after an SGDS-K score ≥8 was defined as depression, the third and the fourth urinary MDA quartiles showed a significantly increased odds ratio(OR) of depression compared to the lowest urinary MDA quartile (third quartile OR, 6.51; 95% CI, 1.77 to 24.00; fourth quartile OR, 7.11; 95% CI, 1.99 to 25.42). Conclusions Our study suggests a significant association between oxidative stress and depressive symptoms in the elderly population.